1993
DOI: 10.1182/blood.v82.10.2937.bloodjournal82102937
|View full text |Cite
|
Sign up to set email alerts
|

Deletions within the LMP1 oncogene of Epstein-Barr virus are clustered in Hodgkin's disease and identical to those observed in nasopharyngeal carcinoma

Abstract: This study of 52 European patients with Hodgkin's disease (HD) expressing the latent membrane protein 1 (LMP1) oncogene within diagnostic Hodgkin and Reed-Sternberg (HRS) cells was performed to detect LMP1 isolates carrying deletions and to characterize them at a molecular and histologic level. Deletions were identified in 5 cases, clustered near the 3′ end of the LMP1 gene, and histologically associated with numerous HRS cells. DNA sequencing showed homology with the deletions seen in the Asian nasopharyngeal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
51
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(53 citation statements)
references
References 0 publications
2
51
0
Order By: Relevance
“…The presence of the del‐ LMP1 genotype, which was originally identified in NPC tissues, in lymphoid malignancies was first reported in a small proportion of European HD cases with histologically aggressive behaviour (Knecht et al, 1993). This association was subsequently extended to other EBV‐related lymphomas from different geographic regions.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…The presence of the del‐ LMP1 genotype, which was originally identified in NPC tissues, in lymphoid malignancies was first reported in a small proportion of European HD cases with histologically aggressive behaviour (Knecht et al, 1993). This association was subsequently extended to other EBV‐related lymphomas from different geographic regions.…”
Section: Discussionmentioning
confidence: 97%
“…cDNA (equivalent to 0.5 μg total RNA) of each case of nasal T/NK‐cell lymphoma, which was used for RT‐PCR analysis of EBV gene expression (Chiang et al, 1996), and 2 μg genomic DNA extracted from frozen tissues of each case of nasopharynx and nasal polyp served as templates for PCR amplification for 40 cycles at an annealing temperature of 56°C. A pair of primers of B95–8 coordinates 168390–168370 and 168075–168095, as described by Knecht et al (1993), was used. Amplified products were electrophoresed through 3% MetaPhor (FMC BioProducts, Rockland, ME) 1 × TAE agarose gel, which was Southern‐blotted by alkaline transfer and hybridised by a 5' end‐labelled internal oligonucleotide probe (B95–8 coordinates 168135–168115) to confirm the specificity.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have revealed that the LMP1 protein of the 30‐bp deletion mutant (del) has a greater potential to transform established rodent fibroblasts and immortalize human keratinocytes in vitro 42 . One study reported on its association with cases of Hodgkin’s disease showing aggressive histology or behavior 43 . Based on these studies, high frequencies of del LMP1 might be expected in certain tumor groups, and del LMP1 may be a predictive factor of clinical outcome.…”
Section: Discussionmentioning
confidence: 99%